Waste Bank Information System in Improving the Economy and Environmental Impact Control in Pari City Village - Muhammad Muttaqin; Mohammad Yusuf; Maya Syaula; Arif Arya Widodo (Yayasan Sinergi Multidimensi Kreatif, 2024)
The Pari City Waste Bank application utilizes a computerized system in managing waste involving the field of information technology. This shows that information technology has become a supporting part in waste management. This waste bank is an institution in the village engaged in waste processing. In addition to saving and sorting waste, the waste bank also teaches the community to process waste into useful goods that have a selling value. A computerized system is needed in waste bank institutions so that their performance can improve and the institution can develop better. From the existing problems, the author created a system for transactions and management of Waste Banks in Pari City using a web-based information system. The results of this web-based Waste Bank application can speed up and make it easier for officers to make transactions, process, and record customer savings data at the waste bank.